A comparative economic assessment of urban transport infrastructure options in low- and middle-income countries. (October 2022) - Vu, Tam; Preston, John
Highlights: Development of a comparative economic assessment of urban mixed transport options. Evaluating the feasibility of new public transport modes (Bus Rapid Transit, Monorail or Metro) in Hanoi, Vietnam. Evaluating impacts of a congestion charge scheme in mixed transport environments. Choosing the most cost-effective mixed transport system in terms of average social cost. Abstract: Several innovative public transport (PT) projects have been developed in low- and middle-income countries (LMICs), where cars, motorcycles and buses share the facilities. However, there seems to be very little evidence on assessment methods to analyse the feasibility of different PT modes and identify the most cost-effective mixed transport system. To address this issue, this study develops a comparative economic assessment (CEcoA) based on the PT technologies' characteristics and the conditions of local transport networks. The assessment integrates four models. First, a social cost model (SCM), that calculates the social costs of each mode and mixed transport systems, is the key model in the assessment. Second, an incremental elasticity analysis (IEA) evaluates changes in total demand by using the demand elasticity with respect to a composite cost. The IEA solves the first drawback of the SCM that demand is assumed to be fixed. Third, an incremental logit model (ILM) estimates changes in modal shares with respect to generalised costs. The ILM overcomes the second disadvantage of the SCM, where preferences of users for all alternative transport modes are not considered. Fourth, a microscopic simulation model (MSM) simulates all existing transport modes' flows on the local network. The MSM solves the third drawback of the SCM, which only considers an isolated corridor without any interaction between the different modes and any junctions. The assessment was applied to compare an existing mixed transport situation and twelve options with an introduction of new PT technologies (Bus Rapid Transit - BRT, elevated Metro and Monorail) replacing the existing bus services; either wholly or partially, and with or without a congestion charge scheme for private transport (PRV) on a corridor in Hanoi, Vietnam in terms of average social cost (ASC), total demand and PT share. The results show that eight options with BRT or Monorail or Metro are feasible, whilst the BRT option that replaces all existing buses and includes congestion charging is the best alternative in terms of ASC. Transport planners and decision makers can draw on the findings of this research. A congestion charge scheme might be considered for the local conditions to meet specific objectives such as a reduction in ASCs and an increase in modal share of PT. The CEcoA can be a strategic tool for not only planning new PT technologies on corridors in the whole network but also retrospectively evaluating investments of PT modes. Moreover, the methodology of the CEcoA might be applied and modified to various transport networks with an abundance of motorcycles to assess the costs and benefits of new PT modes and mixed transport systems with or without the congestion charge.